A novel platform for engineered AAV-based vaccines - Sabrina Babutzka; Miranda Gehrke; Anastasia Papadopoulou; Maria Diedrichs-Möhring; Maria Giannaki; Lena Hennis; Bastian Föhr; Cale Kooyman; Andreas Osterman; Evangelia Yannaki; Gerhild Wildner; Hermann Ammer; et al. (Molecular Therapy: Methods & Clinical Development)
Engineering of adeno-associated virus (AAV) capsids allowed for the development of gene therapy vectors with improved tropism and enhanced transduction efficiency. Capsid engineering can also be used to adapt the AAV technology for applications outside gene therapy. Here, we investigated modified AAV capsids as scaffolds for the presentation of large immunogenic antigens to elicit a strong and specific immune response against pathogens. Using SARS-CoV-2 as a model pathogen, we introduced ∼200 amino acids of the SARS-CoV-2 receptor-binding domain (RBD) into a surface-exposed variable loop region of AAV2 and AAV9, resulting in AAV2.RBD and AAV9.RBD capsids (AAV.RBDs). This engineering endowed AAV.RBDs with SARS-CoV-2-like properties, such as angiotensin-converting enzyme 2 receptor affinity. In line with this, AAV.RBDs were neutralized by sera from human donors vaccinated against SARS-CoV-2. When administered subcutaneously to rabbits, AAV.RBDs elicited a strong humoral response against SARS-CoV-2 RBD. Moreover, the AAV.RBDs were able to trigger RBD-specific cellular immune responses in peripheral human lymphocytes. In conclusion, this novel AAV-based next-generation vaccine platform allows for the presentation of large antigenic sequences to elicit strong and specific immune responses. This versatile vaccine technology could be explored in the context of diseases where conventional immunization approaches have been unsuccessful.